2005
DOI: 10.1111/j.1551-2916.2005.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Mechanically Activated Tetracalcium Phosphate

Abstract: Prolonged high‐energy ball milling of tetracalcium phosphate (TTCP) resulted in a mechanical activation with the formation of nanocrystalline or amorphous domains within the compound. This mechanically activated material demonstrated a completely different thermal behavior compared with highly crystalline TTCP. Differential scanning calorimetry (DSC) measurements indicated the presence of exothermic reactions between 370° and 480°C and between 630° and 930°C for 24 h‐milled TTCP, which could be related to conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, single-component TTCP cements can be obtained after prolonged ball-milling, leading to partial amorphization (mechanical activation) of the material [12,[31][32][33]. This strongly increases both the kinetic solubility (rate of dissolution) as well as the thermodynamic solubility product, such that setting occurs even at room or body temperature.…”
Section: Single-component Ttcp Cementsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, single-component TTCP cements can be obtained after prolonged ball-milling, leading to partial amorphization (mechanical activation) of the material [12,[31][32][33]. This strongly increases both the kinetic solubility (rate of dissolution) as well as the thermodynamic solubility product, such that setting occurs even at room or body temperature.…”
Section: Single-component Ttcp Cementsmentioning
confidence: 97%
“…At low temperatures, this apatitic phase may be phosphate deficient as a result of the incomplete decomposition. Thermal analysis using differential scanning calorimetry (DSC) showed an endothermic peak at 750°C in the pattern of mechanically activated TTCP, which may be attributed to a combination of the transformation of this non-stoichiometric apatite phase to stoichiometric HA and crystalline CaO [32]. In order to confirm further that mechanical activation was responsible for the decomposition of TTCP at temperatures as low as 200°C, DSC measurements were performed on mechanically activated TTCP which had been hydrolysed to CaO and HA at room temperature in water.…”
Section: Thermal Behaviourmentioning
confidence: 99%
“…Other authors have shown that a prolonged high-energy ball milling of either α-TCP, β-TCP powder in ethanol or a dry mixture of ACP and DCPD powders lead to ACP formation after 24 h [156][157][158]. Furthermore, prolonged high-energy ball milling of TTCP was found to result in a mechanical activation with the formation of undisclosed nanocrystalline and/or amorphous domains within the compound [159]. However, there is a non-negligible risk of powder contamination (ball wear) when using this processing route over extended periods to obtain an ACP [31].…”
Section: Mechanical and Pressure-induced Techniquesmentioning
confidence: 98%
“…7 However, because the additives have limited solubilities, amorphous calcium phosphates with Ca/P molar ratios similar to and/or larger than that of apatite are needed for the preparation of intelligent calcium phosphate cement. Although a few research groups have actually proposed synthetic routes for amorphous calcium phosphates with large Ca/P molar ratios, 26,27 a facile synthetic approach is needed for the further design of such materials.…”
Section: Introductionmentioning
confidence: 99%